Calculation of Stabilization Energy of Tetrahedrane with its Nitrogen Substituted Derivatives by DFT Method and Driving an Empirical Relation Connect it with Charge Functions of the Molecule - Fatimah Ayad Abdul Jabbar (Journal of Global Pharma Technology, 2019)
In this work the strain energy of tetrahedrane and its nitrogen substituted molecules were calculated by isodesmic reaction method according to DFT quantum chemical fashion, the used basis set was 6-31G/B3-LYP, in addition all structures were optimized by RM1 semi-empirical method. From the obtained data we estimate an empirical equation connect between strain energy of the molecule with charge functions represented by dipole moment of the molecule plus accumulated charge density involved within the tetrahedron frame plus the number of nitrogen atoms. The results indicate the charge spreading factors by polarization and 14nâ†’Ïƒ*">  processes are the most important factors in decreasing the strain energy.Keywords: Tetrahedrane, Azaetrahedranes, Isodesmic reaction, Strain energy.